ANALISIS PENGARUH AUDIT INTERNAL DAN PENGENDALIAN INTERNAL TERHADAP PENCAPAIAN GOOD GOVERNANCE - , ALFIAN ANDRE YULIANTO BUMBUNGAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to analyze the impact of internal audit and internal control towards good governance achievement in State University at D.I.Yogyakarta. Those State Universities are Universitas Gadjah Mada, Universitas Negeri Yogyakarta, Universitas Islam Negeri Sunan Kalijaga dan Institut Seni Indonesia. Respondents of this research are population of entire internal auditor at those four institutions. Measurement of this internal audit variable is using factors that stated by Standar Professional Audit Internal, which are independency, professional competencies, area of work, and committee of examination. Whereas, measurement of internal control variable is using factors that stated by Comitte of Sponsoring Organization of the Treadway Comission (COSO), which are control area, risk valuable, control activity, information and communication, and monitoring good governance with main guidience factors by Komite Nasional Kebijakan Governance (KNKG). Those factors are transparency, accountability, responsibility, independency, fairness and equality. The result shows that there are positive connections between internal audit and internal control into good governance.